Eco-Hijaiyah: Learning Arabic Letters through Leaf Media for Children Aged 4-5 Years - Risma Qurrotu A'yun; Nelva Rolina (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This study aims to address the challenge that young children aged 4–5 years often have difficulty recognizing and connecting Hijaiyah letters when conventional media, such as printed cards and blackboards, are used, leading to low engagement and rote memorization. To fill this gap, the study introduces the Eco-Hijaiyah approach, a nature-based learning method that utilizes leaf media to integrate religious and ecological values through fun, hands-on activities. The research employed a Classroom Action Research (CAR) design, based on Kemmis and McTaggart, and was conducted in two cycles with 12 children as participants. Data were collected through structured observations assessing children’s ability to recognize, pronounce, arrange, and connect Hijaiyah letters. The findings show a significant improvement from the category of Developing (56%) in Cycle I to Highly Proficient (83%) in Cycle II. This demonstrates that Eco-Hijaiyah through leaf media effectively enhances early childhood Hijaiyah literacy while simultaneously fostering spiritual awareness, environmental appreciation, and experiential engagement. The study contributes to the early childhood education literature by providing a novel, eco-literacy-integrated approach to learning Arabic letters.